Translocation of trapped Bolivian river dolphins (Inia boliviensis) - Aliaga- Rossel, Enzo; Escobar-ww, Mariana (The journal of cetacean research and management, 2020)
The Bolivian river dolphin (Inia boliviensis), locally known as bufeo is an endemic species and categorized as Vulnerable in the Red Book of Vertebrates of Bolivia. Despite the fact that the Bolivian river dolphin is the only cetacean in land-locked Bolivia, knowledge about its conservation status and vulnerability to anthropogenic actions is extremely deficient. We report on the rescue and translocation of Bolivian river dolphins trapped in a shrinking segment of the Pailas River, Santa Cruz, Bolivia. Anthropogenic activities to alter the landscape and create agricultural land in the area include significant deforestation and irrigation channel construction and are likely to be a contributory factor causing the entrapment of these Bolivian River dolphins. The dolphins were trapped in shallow water in a 1 km section of river. Dry season water levels were rapidly falling and this section of river dried up completely.  We collaborated with several institutions, authorities, and volunteers to translocate 26 Bolivian river dolphins, including calves, juveniles, and pregnant females. The dolphins were captured and transported using well-padded boats and vehicles and released into the Rio Grande. Each dolphin was accompanied by biologists who assured their welfare. No dolphins were injured or died during this process. If habitat degradation continue, it is likely that events in which river dolphins become trapped in South America may happen more frequently in the future.